DEVELOPMENT OF TRANSPORT AND COMMUNICATION IN THE VALLEY OF KASHMIR FROM 1885 A.D-1925 A.D - Reyaz Ahmad Bhat (RADJA PUBLIKA, 2022)
This research paper explores the transformative journey of the transport and communication systems in the Valley of Kashmir during the period from 1885 to 1925. The paper delves into the historical context, examining the pivotal role played by various factors in shaping the region's transportation infrastructure and communication networks. Through a comprehensive analysis of primary and secondary sources, this study highlights the impact of technological advancements, political changes, and economic considerations on the evolution of transport and communication in the Valley of Kashmir.